(3fXe eSGfOI GdbQGQGJ HGYJeGO GdHQeLjI GdLGgRIs - (3eMeO YHO MSjf(B, (3GdWGFjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2008)
(3fXe eSGfOI GdbQGQGJ (B: (3GdfThA h Gdeaghe h GdNUGFU , CfhGY fXe eSGfOI GdbQGQGJ h COhGJgG h JWHjbGJgG , GdGfXeI GdaQYjI dfXe eSGfOI GdbQGQGJ , eOGNd JWhjQ h eQGMd JUeje h HfGA fXe eSGfOI GdbQGQGJ , OhQ fXe eSGfOI GdbQGQGJ aj UfY GdbQGQGJ GdGOGQjI , cjajI GYJeGO JWHjbGJ fXe eSGfOI GdbQGQGJ(B.s
(3eQGLY U(B.229s
Keywords: (3EOGQI GdGYeGds; (3GJNGP GdbQGQGJs; (3GdbQGQGJ GdGOGQjIs